Pembangkit Listrik Tenaga Airwalker (Alat Fitnes) Sebagai Sumber Energi Alternatif - WAHYU SUGIYONO, ARIF; ARIS BUDIMAN, ST,MT (2016)
The use of electrical energy increases with population growth so that the supply led to oblige. Around us there are sources of energy buses in use , whether large or small. Airwalker is one type of fitness equipment that is biased in use of energy. This research was conducted in the welding workshop .These testing tools include among others multimetester , tachometer ,lumenmeter and tools for designing the framework Airwalker. The design of this Airwalker using steel beams with a thickness of 2 . Airwalker Power Plant is designed with both in order to rotate the flywheel to the maximum , because the swing Airwalker used as an early mover . DC Generator generator system utilized . The results of the test voltages and currents that generate dependency on flywheel rotation in moving the generator DC. On lap 400 RPM can be generated voltage and current 53V 0.47A. The turbine system will be able burdened LED lamps of 25 watts.